Amnionless function is required for cubilin brush-border expression and intrinsic factor-cobalamin (vitamin B(12)) absorption in vivo - He, Qianchuan (The American Society of Hematology, 2005)
Amnionless (AMN) and cubilin gene products appear to be essential functional subunits of an endocytic receptor called cubam. Mutation of either gene causes autosomal recessive Imerslund-Gräsbeck syndrome (I-GS, OMIM no. 261100) in humans, a disorder characterized by selective intestinal malabsorption of cobalamin (vitamin B(12)) and urinary loss of several specific low-molecular-weight proteins. Vital insight into the molecular pathology of I-GS has been obtained from studies of dogs with a similar syndrome. In this work, we show that I-GS segregates in a large canine kindred due to an in-frame deletion of 33 nucleotides in exon 10 of AMN. In a second, unrelated I-GS kindred, affected dogs exhibit a homozygous substitution in the AMN translation initiation codon. Studies in vivo demonstrated that both mutations abrogate AMN expression and block cubilin processing and targeting to the apical membrane. The essential features of AMN dysfunction observed in vivo are recapitulated in a heterologous cell-transfection system, thus validating the system for analysis of AMN-cubilin interactions. Characterization of canine AMN mutations that cause I-GS establishes the canine model as an ortholog of the human disorder well suited to studies of AMN function and coevolution with cubilin. (Blood. 2005;106:1447-1453)